Pressure Group on Forest and Land Fire Policy in Riau Province 2019 (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
Forest and land fires in Riau Province for the period of 2019 caused enormous losses, many aspects were disturbed by the fires, namely economic, health and bilateral relations which were most affected. Meanwhile, the government seems slow in dealing with forest and land fires and resolving their impacts. The slow pace of government action has prompted groups outside the government to participate in efforts to accelerate the handling of forest and land fires in Riau. From this background, this study looks at the role of groups outside the government (pressure groups) in encouraging the acceleration of forest and land fire prevention in Riau in 2019. This study uses a qualitative approach with descriptive data analysis. Sources of data were obtained from interviews, review of legal products, articles, related documents and news sources from the mass media. This research shows that the existence of the student action movement, environmental activists and other civil society organizations, is able to accelerate the government to take preventive and curative actions to tackle forest and land fires in Riau Province. The presence of this pressure group is also a bridge of interests between the people and the state so that corrections to inappropriate state policies can be immediately carried out to prevent forest and land fires.